Pirfenidone Inhibits Proliferation and Promotes Apoptosis of Hepatocellular Carcinoma Cells by Inhibiting the Wnt/β-Catenin Signaling Pathway - Zou, Wei-Jie (Med Sci Monit, 2017)
BACKGROUND: Hepatocellular carcinoma (HCC) is the most important cause of cancer-related deaths worldwide. Pirfenidone is an orally available small molecule with therapeutic potential for fibrotic diseases. MATERIAL/METHODS: In this study, we analyzed the effects of different pirfenidone concentrations on the proliferation of HepG2 HCC cells using Cell Counting Kit-8 (CCK-8) and colony formation assays. Flow cytometry was performed to measure the apoptotic effects of pirfenidone on HepG2 cells. Western blot analysis was performed to detect the expression of β-catenin and p-β-catenin. RESULTS: Pirfenidone inhibited proliferation and promoted HepG2 cell apoptosis. In addition, Western blot results indicated that pirfenidone suppressed β-catenin expression in HepG2 cells. To assess the mechanism, we treated HepG2 cells with pirfenidone, and pirfenidone plus the β-catenin activator, SB-216763. The results revealed that SB-216763 accelerated proliferation and inhibited apoptosis in HepG2 cells treated with pirfenidone. Western blot results showed that SB-216763 upregulated β-catenin expression in HepG2 cells treated with pirfenidone. CONCLUSIONS: In conclusions, pirfenidone may be a potential drug for HCC treatment.